Review Ketepatan Kode Diagnosis Dan Pending Klaim Rekam Medis Pasien Covid-19 Tahun 2021 - Laili Rahmatul Ilmi; Ratna Prahesti; Praptana Pratana; Ayu Wahyuningsih; Chinara Manuela (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
A complete of medical record and the accuracy of clinical coding is reflect to the quality of medical record documentation. In 2021, the number of pending claim for medical record patient’s covid-19 is 41%, as cause the quality of medical record incomplete. The research aim is to measure the quality of medical records by covid-19 documentation for pending claims and the accuracy of coding Covid-19. The research method is mixed-method sequential explanatory. We used the checklist observation to measure the quality of clinical coding for patient covid-19 and interview guideline to explore the factors of pending claims. The total sampling are 889 of medical records as secondary data was analyze with STATA Version 13. The characteristic of administrative data by gender is man 571 (64,45%), woman 315 (35,35%). the number of classification covid-19 case is probable 25 cases (2,71%), suspected 214(24,15%) and confirmed 648 cases (73,14%). In another hand, the quality of accuracy coding covid-10 use code B34.2 is 377 (42,55%), use code U07.1 is 295(33,30%) and use code Z20.8 is 215 (24.14%). The accuracy of coding covid-19 is 295 (33,30%) and inaccurate 591 (66,70%). we observe the number of pending claims is 222 due to incomplete of signature and full name of physician items in discharge summary form.